Developing writing skills for IELTS aresearch-based approach - Chong, Sin Wang; Ye, Xuejun (Routledge, Taylor & Francis Group, 2021)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Support Material -- Acknowledgements -- Part I -- Chapter 1: Introduction to IELTS and IELTS Writing -- Chapter 2: Use of Exemplars: Q&amp -- A on Theory and Research -- Chapter 3: Task 1: Task Achievement -- Chapter 4: Task 1: Coherence and Cohesion -- Chapter 5: Task 1: Lexical Resource -- Chapter 6: Task 1: Grammatical Range and Accuracy -- Chapter 7: Task 2: Task Achievement -- Chapter 8: Task 2: Coherence and Cohesion -- Chapter 9: Task 2: Lexical Resource -- Chapter 10: Task 2: Grammatical Range and Accuracy -- Chapter 11: Task 1: Exemplar Analysis by Question Types -- Chapter 12: Task 2: Exemplar Analysis by Question Types -- Chapter 13: Question Bank -- Part II -- Answers to Chapter 3: Task 1: Task Achievement -- Answers to Chapter 4: Task 1: Coherence and Cohesion -- Answers to Chapter 5: Task 1: Lexical Resource -- Answers to Chapter 6: Task 1: Grammatical Range and Accuracy -- Answers to Chapter 7: Task 2: Task Achievement -- Answers to Chapter 8: Task 2: Coherence and Cohesion -- Answers to Chapter 9: Task 2: Lexical Resource -- Answers to Chapter 10: Task 2: Grammatical Range and Accuracy -- Index
Keywords: Englisch; Sprachtest; Schreiben